2018
DOI: 10.1002/clen.201700653
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Inhibition on Anaerobic Digestion of Animal Manure and Controlling Strategies: A Short Review

Abstract: Despite the efficacy of anaerobic digestion (AD) in stabilizing animal wastes as well as alleviating global warming associated with natural decomposition of animal manure, the process is susceptible to antibiotics that commonly exist in animal manure. Although antibiotics have served veterinary purposes in large quantities for decades, knowledge concerning their impacts on methane production during AD of animal manure is still in its infancy. Antibiotics used in animal practice are recognized as one of the maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 90 publications
0
4
0
1
Order By: Relevance
“…This phenomenon may be explained by the greater quantity of undigested organic matter in the manure (Benjamin & Weelden, 2014), which serves as a nutrient source for methanogens. The abundance of methanogens may also be by other factors, like manure depth (Barret et al, 2013), amount of VFAs (Gorris et al, 1989), competition from other microbes (Shaw et al, 2019), the presence of antibiotics (Yang et al, 2019), or whether residual manure remains after emptying the manure pits (Habtewold et al, 2018). This study's results are consistent with the idea that high amounts of VFAs, specifically butyric acid, isobutyric acid, and acetic acid, indicate low level of acetotrophic methanogenesis in non-foaming manure samples.…”
Section: Biogas Productionmentioning
confidence: 99%
“…This phenomenon may be explained by the greater quantity of undigested organic matter in the manure (Benjamin & Weelden, 2014), which serves as a nutrient source for methanogens. The abundance of methanogens may also be by other factors, like manure depth (Barret et al, 2013), amount of VFAs (Gorris et al, 1989), competition from other microbes (Shaw et al, 2019), the presence of antibiotics (Yang et al, 2019), or whether residual manure remains after emptying the manure pits (Habtewold et al, 2018). This study's results are consistent with the idea that high amounts of VFAs, specifically butyric acid, isobutyric acid, and acetic acid, indicate low level of acetotrophic methanogenesis in non-foaming manure samples.…”
Section: Biogas Productionmentioning
confidence: 99%
“…Sulfonamides are the most used type of antibiotics in the pig industry, especially sulfadiazine (SDZ), with concentrations in the order of 91-235 mg / L found in pig manure according to Yang et al (2019). In one study carried out by Huang et al (2019), 5.0 g / L of ZVI significantly optimized the acidification process, enriching the bacteria Clostridia and Bacteroidia, which are mainly responsible for producing VFA and H2, providing greater substrate availability for methanogenesis.…”
Section: The Use Of Mineral Additives To Optimize the Anaerobic Digestion Process In Pig Farming Systemsmentioning
confidence: 99%
“…Antibiotics are used in therapeutic or sub-therapeutic doses on animal farms, including swine farms, to prevent infections and treat disease (Yang et al, 2019). Spielmeyer (2018) reported that was possible to recover from <5 to 90%, depending on the antibiotic class, of the active substances in waste excreted by the animals because these compounds may not be completely metabolized.…”
Section: Effect Of Antimicrobials and Their Persistence In Digestatesmentioning
confidence: 99%